Blockchain and Islamic Social Finance: A Systematic Review of Technological Innovation in Social Institutions in Indonesia (International Forum of Researchers and Lecturers, 2025)
Zakat and waqf are integral components of the Islamic social finance system, intended to promote social equity and empower underserved communities. In Indonesia, however, the management of these instruments continues to encounter obstacles, particularly concerning transparency, accountability, and public confidence. With technological advancements, blockchain has emerged as a transformative tool with the potential to enhance the governance of Islamic philanthropic institutions. This study systematically reviews 68 scholarly articles published between 2016 and 2025 to explore the opportunities and limitations of adopting blockchain technology in Indonesia’s zakat and waqf sectors. The review identifies four central themes: improving transparency and accountability; increasing operational efficiency and optimizing waqf asset utilization; building public trust; and assessing institutional readiness for digital transformation. The findings suggest that blockchain aligns well with Sharia principles by enabling real-time financial reporting, facilitating smart contract implementation, and offering reliable data-driven asset tracking. Despite these advantages, widespread adoption remains constrained by regulatory uncertainty, limited digital literacy, and insufficient technological infrastructure. To address these challenges, the study highlights the need for collaborative efforts among government bodies, zakat and waqf institutions, and technology developers to create a more transparent, inclusive, and sustainable digital Islamic social finance ecosystem. Such cooperation is seen as essential not only for advancing governance standards but also for reinforcing the public’s trust in religious financial institutions. By leveraging blockchain, Indonesia has the opportunity to modernize its zakat and waqf management systems while preserving the core ethical and spiritual values embedded in Islamic finance. Ultimately, the study underscores that while blockchain holds significant promise, its successful implementation will depend on aligning technological innovations with institutional capacity and regulatory frameworks.